Soldagem de ligas de alta entropia por TIG - Lobo, Tiago de Oliveira (Universidade Federal de São Carlos, 2024)
This work provides a comprehensive approach to Tungsten Inert Gas (TIG) welding of high-entropy alloys (HEAs), exploring both theoretical and practical aspects in this emerging field. The literature review highlighted the complexity of HEAs, their diverse nomenclatures, and conceptual challenges related to the lack of a precise definition. The analysis of HEA properties revealed the dynamic interaction between entropy and enthalpy, emphasizing the competition between these factors in determining the predominant phases. Central effects identified by Yeh, such as high entropy, lattice distortion, slow diffusion, and the cocktail effect, were discussed in detail, pointing out some inconsistencies in this concept. It was emphasized that multiple-component alloys cannot be analyzed as a group of steels due to their much broader range of possibilities. In the welding context, the review focused on the application of HEAs as base materials and consumables. Studies showed promising results, with the AlxCoCrFeNi alloy being widely investigated. Tensile strength, plasticity, and structural stability were analyzed under different welding conditions, highlighting the importance of controlling the cooling rate and chemical composition. However, challenges such as crack formation in copper-added alloys and the need for heat treatments to optimize properties require further attention. The correlation between theory and practice, especially regarding microstructure, remains a significant point, emphasizing the need for additional studies to consolidate relationships between welding parameters and final properties. Moreover, the quest for cost reduction strategies, such as the incorporation of iron and controlled copper addition, proves vital to enable practical applications of these alloys in various sectors. Balancing alloy performance with economic feasibility is a fundamental consideration for widespread adoption. In conclusion, TIG welding of HEAs represents a promising research field due to the existence of alloys demonstrating excellent properties and the potential emergence of more alloys with equally or even better properties. However, it requires overcoming technical challenges and deepening theoretical-practical understanding. The contributions presented in this literature review offer valuable insights for researchers, engineers, and industry professionals seeking to explore and apply these innovative materials.
TIG welding of high entropy alloys
Keywords: Liga de alta entropia; Liga de multicomponente; Soldagem; Microestrutura; TIG; High-entropy alloys; Multi principal element alloys; Welding; Microstructure; Tungsten Inert Gas; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA